ANALISIS BIBLIOMETRIK ASIMETRI INFORMASI PADA PASAR SAHAM - Yasinta Dewi Umi Latifah; Teguh Sriwidjayanto (LPPM STIE Muhammadiah Bandung, 2022)
Information is one of the important parameters for investors to invest in the capital market. However, it cannot be denied that there is a phenomenon of some incorrect information related to the condition of the issuer and other things that affect liquidity, activity and share volatility which is called information asymmetry. The phenomenon of information asymmetry in the stock market is interesting to study, so researches that analyze information asymmetry and the stock market have begun to develop. The purpose of this study is to analyze the development of research related to information asymmetry in the stock market which will later be useful for recommendations for further research. This study uses a qualitative method utilizing Publish or Perish software, Google Scholar, VOSViewer and Biblioshiny R-package through a systematic, explicit and reproductive method approach. The data used is a database from Google Scholar related to the topic specified from 2019 to 2022. Based on the research conducted by the author, it is known that there are 5 vocabulary clusters that are often used in research and vocabulary that is rare or has the potential for further research related to the level of information asymmetry in the stock market.